Al-doped ZnO mechanical milled powders for dye sensitized cells - Damonte, Laura Cristina (2010)
Mixtures of Al2O3 and ZnO powders were prepared by mechanical milling. The resulting samples were analyzed and characterized by X-ray diffraction (XRD), positron annihilation lifetime spectroscopy (PALS), scanning electron microscopy (SEM) and optical reflection spectroscopy (OPS). XRD and PALS measurements confirm Al incorporation into ZnO wurtzite structure. Powders obtained from Al2O3 precursors display better reflectivity than those prepared from Al metal so they might be better materials for implementation in photovoltaic solar devices.